New long-term mass-balance series for the Swiss Alps - Huss, Matthias; id_orcid:0 000-0002-2377-6923; Dhulst, Laurie; Bauder, Andreas; id_orcid:0 000-0001-7197-7706 (Journal of Glaciology, 2015)
ISSN:0022-1430 ISSN:1727-5652